2013
DOI: 10.2967/jnumed.112.113183
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism in 18F-FDG PET Predicts Favorable Outcome Following Decompressive Surgery in Patients with Degenerative Cervical Myelopathy

Abstract: The aim of this study was to prospectively assess the regional changes of glucose metabolism of the cervical spinal cord in patients with degenerative cervical spine stenosis and symptomatic cervical myelopathy after decompressive surgery using 18 F-FDG PET. Methods: Twenty patients with symptomatic degenerative monosegmental cervical stenosis with neuroradiologic signs of spinal cord compression underwent decompressive surgery. The clinical course using a functional status score (Japanese Orthopedic Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The fact that microglia are activated in CSM was expected and corresponds well with findings of other CSM models [22, 24, 28, 51] and post mortem studies of CSM [51]. Similarly, PET studies conducted in clinical patients confirmed that cord compression in CSM is associated with inflammation [18]. …”
Section: Discussionsupporting
confidence: 82%
“…The fact that microglia are activated in CSM was expected and corresponds well with findings of other CSM models [22, 24, 28, 51] and post mortem studies of CSM [51]. Similarly, PET studies conducted in clinical patients confirmed that cord compression in CSM is associated with inflammation [18]. …”
Section: Discussionsupporting
confidence: 82%
“…10 Early-stage myelomalacia may be reversible, depending on the severity of the initial SCI, 14 and may be reversed after decompression surgery. 15 Anecdotally, based on these fi ndings as well as debates at spine meetings, some spine surgeons in North America advocate pre-emptive surgical decompression to prevent such catastrophic injuries or clinical progression in these patients. To our knowledge, however, the overall prevalence of cervical myelomalacia based on a large study is unknown.…”
mentioning
confidence: 99%
“…A threat to succinct guidelines would include attempts to future proof them. As already mentioned, the ambiguity of co-morbidities is one example, but also the inclusion of promising new imaging techniques not captured in this systematic review, such as PET [ 28 ] and Diffusion Tensor Imaging [ 29 ]. Future-proofing is extremely difficult and may risk overcomplicating reporting at this time.…”
Section: Discussionmentioning
confidence: 99%